Impoliteness Strategies in John Mulaney's Stand-Up Comedy - Arlivia, Zitta; Sembodo, Thomas Joko Priyo (Universitas Gadjah Mada, 2024)
An analytical study on comedy provides significant insight into comedy as a complex and pervasive medium of expression penetrating everyday life. This study investigates the impoliteness strategies in John Mulaney’s stand-up comedy and how the most frequently used strategy entertains the audience through five sources of pleasure. The data gathered are the utterances containing impoliteness strategies from John Mulaney’s stand-up comedy specials: New in Town (2012), The Comeback Kid (2015), Kid Gorgeous (2018), and Baby J (2023). The impoliteness strategies found in the stand-up comedy were then classified using the theory of impoliteness strategies proposed by Culpeper (1996). The data containing the most frequently used impoliteness strategy are then classified based on Culpeper’s (2011) theory of five sources of pleasure of entertaining impoliteness function. The result shows 344 impoliteness strategies, with the positive impoliteness strategy being the most frequently used, with 163 occurrences (47.4%). From the 163 occurrences of positive impoliteness strategies, 105 entertain the audience through emotional pleasure (64%), followed by the pleasure of being superior with 33 occurrences (20.1%), the pleasure of feeling secure with 14 occurrences (8.5%), voyeuristic pleasure with ten occurrences (6.1%), and aesthetic pleasure with two occurrences (1.2%). The findings indicated that throughout his stand-up comedy performances, John Mulaney employs various impoliteness strategies, especially positive impoliteness strategies, to entertain the audience, primarily by evoking their emotional pleasure.